On Adding Support for Real-Time and Distributed Applications to the MatPLC - Mário de Sousa (2004)
The MatPLC is an open-source control application, consisting of a core, generic modules,and tools for creating custom modules. Since many control and monitoring systems are distributedin nature and require strict time detenninism, features not currently supported, the addition of hardteal-time capabilities as well as support for distributed applications is required. The paper includesan outline of the MatPLC's architecture, and details the design changes required to add hard realtimecapabilities to the MatPLC framework. The IEC 61131-3 compiler is presented, and adiscussion is made regarding how it may be extended to support the IEC 61499 standard fordistributed applications.